The Correlation between Information Quality and User Satisfaction of the Hospital Management Information System - Suandari, Putu Vierda Lya; Suasnawa, I Gede; Nugraha, I Nyoman Adikarya; Sutrisnawati, Ni Nyoman Dwi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Hospital Management Information System (HMIS) is a system of communication and information that processes and integrates the entire flow of hospital service in a network of coordination, reporting and administrative procedures to obtain accurate information. Integrated HMIS will help speed up the hospital management process. Purpose: To determine the correlation between the quality of information produced by HMIS and user satisfaction in terms of the benefits generated at Balimed Hospital Denpasar. Methods: This research used a quantitative method by administering a questionnaire. The number of samples was 69 respondents HMIS users from 15 unit in the hospital with Proportionate Random Sampling technique. Data was collected using a questionnaire with the sample participating in answering several questions in this research questionnaire. Spearmans Test was conducted for Hypothesis testing. Results: Variable of information quality has good category with overall average value is 2.71. The statement with the highest average value is